Performance of spark-ignition engine at various fuel octane numbers - Prihatno, Anton; Hendrawan, Andi (Applied Research and Smart Technology (ARSTech), 2021)
The paper describes the performance of a spark-ignition engine at various fuel octane numbers. This study was realised using a 150cc automatic motorcycle with a compression ratio of 10.6:1. The experiments were conducted on three types of gasoline with different research octane numbers (RON), namely 88, 90, and 92. The torque and power of the engine were evaluated using a dyno test, while fuel consumption was simultaneously monitored during the experiments. The data were then collected and analysed using Motorcycle Communication System (MCS). The MCS measurements indicated that fuel with RON 92 allows the vehicle to reach the top speed and rotation at a gas opening angle of 25° - 79°. Applying fuel with the proper octane number in an engine with a particular compression ratio can maintain optimal engine performance. Decreasing the fuel's octane rating from the recommended conditions based on the engine specifications causes a decrease in engine performance. Torque and power tend to drop, and fuel is not economical.